(897) التوازن الاقتصادى وحتمية الحل اللاشتراكى (بحث فى إعادة تقييم فاعلية السياسات الاقتصادية) Economic equilibrium and the inevitability of a non-socialist solution (a study in re-evaluating the effectiveness of economic policies) - السيد, عاطف (معهد التخطيط القومى, 2024)
يحاول البحث تحليل ما إذا كان النظام الرأسمالي محكومًا بالتقلبات الاقتصادية وعدم الاستقرار، حتى مع تدخل الدولة لتوجيه المتغيرات الاقتصادية، مع التركيز على الأساس الفردي للاقتصاد. يستعرض البحث جدلية تاريخية بين رأيين: الأول، تبناه ماركس والماركسيون، يرى أن الرأسمالية تؤدي حتمًا إلى أزمات اقتصادية كما أثبتت أزمة 1929. الثاني، يعتقد أن تدخل الدولة وتوجيه الاقتصاد يمكن أن يخفف أو يمتص آثار التقلبات. يناقش البحث هذه الأفكار في ضوء التجارب التاريخية مع التركيز على جدوى الاشتراكية كحل بديل لتحقيق الاستقرار الاقتصادي./ / The study explores whether the capitalist system is inherently prone to economic fluctuations and instability, even with state intervention to regulate economic variables, given its reliance on individual initiatives. It examines the historical debate between two perspectives: the first, proposed by Marx and Marxists, argues that capitalism inevitably leads to crises, as evidenced by the 1929 Great Depression. The second posits that state intervention and accurate economic forecasting can mitigate or absorb the effects of such fluctuations. The study evaluates these viewpoints with an emphasis on socialism as a potential alternative for achieving economic stability.